Sosialisasi Pengolahan Air Limbah Kolam Ikan Nila Dengan Menggunakan Tanaman Akar Wangi Di RW 4 Poharin Malang - Wulandari, Lies Kurniawati; Indra, Dimas (STIE Malangkucecwara, 2025)
Wastewater is a type of wastewater that comes from bathroom and washing water which enters the drainage and is added to rainwater which flows downstream into the river. In this case, the aim is to increase the effectiveness of greywater liquid waste processing by using a physical model consisting of a processing process, namely a vetiver wetland filter. The expected result is that the use of a physical model consisting of a vetiver wetland with or without media is able to improve the quality of waste water, where the resulting output meets water quality standards (bath water or clean water). Thus, overall it can be concluded that the use of the physical waste processing model applied is able to reduce the pollutants contained in greywater waste